THE RELATION OF FUNCTION TO PRINCIPLES. - Littleton, A. C. (The Accounting Review, 1938)
Abstract A review of the accumulated criticisms of the American Accounting Association's "Tentative Statement of Accounting Principles" shows that points made are of two kinds, those concerned with various details and those expressing fundamental differences in point of view. Criticisms raise certain fundamental issues. For example, are accounting principles related to the function of accounting, and if so, what is that function? Are accounting principles to restrict or liberate managerial freedom to deal with changing conditions? In discussions of function there is a tendency to confuse central purpose with possible uses. Uses to which accounting data may be put are many and diverse, obviously, principles and procedure cannot be oriented equally well to all uses, nor can each use have its own set of principles and procedure. It may be said that accounting serves several purposes. If some of these purposes are in conflict, as they are very likely to be, accounting is then pulled this way by one interest and that way by another, and as a result one cannot say that a corporation's financial statements are continuously in accord with a single coordinated body of accounting theory.